REFUSAL STRATEGIES BY JAVANESE TEACHERS - Retnowaty Retnowaty (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
Refusal is one of many speech acts investigated in pragmatics. We usually do it in our life to reject other person’s request. People from different culture usually employ different refusal strategies since every culture has various way in protecting their positive face and reducing the threat that occur because of refusal ((Brown & S. Levinson, 1987). This study has two objectives: 1) to find out kind of strategies are used by Javanese teacher in performing refusal; 2) to describe how Javanese teacher use refusal strategies regarding the status of the addressee. This study was a qualitative study. The data were collected using discourse completion task (DCT) to elicit compliment responses from 16 teachers in Airlangga Junior High School Balikpapan. The discourse completion task (DCT) encompasses a variety of situations that required the participants to refuse the requests directly at them. Moreover, the data were analyzed with the help of Bebe, et all. (1990) in (Boonkongsaen, 2013) indicators. We can inferred that most participants used difference of refusal strategies. However, most participants tended to use the indirect strategies. Finally, this study also showed that the participants were more likely to be polite in their way of refusing requests.